PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII2 SMP NEGERI 2 SUNGAI APIT - Zuraini, Dina; ', Syofni; Yuanita, Putri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was based on the students achievement in learning mathematics especially grade VIII2 of SMP Negeri 2 Sungai Apit under the Mastery Minimum Criteria with percentage of 40,74% on the test about Tribe Factorization Algebra. This research is a class action research. This research aims to improve the learning process and improve learning result in mathematics in grade VIII2 of SMP Negeri 2 Sungai Apit by that applying the cooperative learning model of structural approach Think Pair Share (TPS). The subject of this research were the students in the class VIII2 of SMP Negeri 2 Sungai Apit that consist of 14 boys and 13 girls at the first semester of academic year 2016/2017. The instruments of data collection in this research were observation sheets and student?s mathematic tests. The activity of teacher and students showed an improvement of learning process prior to the action on the first and second cycles. The results of this research showed an increasing number of students learning mathematic from the basic score with percentage 40,74% to 59,25% on the first test and 70,37% on second test. The frequency distribution analysis as well showed an improvement student achievement are increasing the number of student who received higher criteria on the first test and second test compared the number of student who received higher criteria on the basic score. On the enaugh criteria, the number of student at interval 41-60 descreased from basic score to the first test and second test. Furtehrmore, on the higher criteria, the number of student at interval 81-100 increased from basic score to first test and second test. Based on the result of this research could be concluded that that applying the cooperative learning model of structural approach Think Pair Share (TPS) can improve the learning process and improve the student?s achievement of learning mathematic in grade VIII2 of SMP Negeri 2 Sungai Apit in the first semester academic years 2016/2017.